Eutectic‐Derived Mesoporous Ni‐Fe‐O Nanowire Network Catalyzing Oxygen Evolution and Overall Water Splitting. Issue 5 (27th September 2017) - Dong, Chaoqun; Kou, Tianyi; Gao, Hui; Peng, Zhangquan; Zhang, Zhonghua
Abstract: The development of efficient and abundant water oxidation catalysts is essential for the large‐scale storage of renewable energy in the form of hydrogen fuel via electrolytic water splitting, but still remains challenging. Based upon eutectic reaction and dealloying inheritance effect, herein, novel Ni‐Fe‐O‐based composite with a unique mesoporous nanowire network structure is designed and synthesized. The composite exhibits exceptionally low overpotential (10 mA cm −2 at an overpotential of 244 mV), low Tafel slope (39 mV dec −1 ), and superior long‐term stability (remains 10 mA cm −2 for over 60 h without degradation) toward oxygen evolution reaction (OER) in 1m KOH. Moreover, an alkaline water electrolyzer is constructed with the Ni‐Fe‐O composite as catalyst for both anode and cathode. This electrolyzer displays superior electrolysis performance (affording 10 mA cm −2 at 1.64 V) and long‐term durability. The remarkable features of the catalyst lie in its unique mesoporous nanowire network architecture and the synergistic effect of the metal core and the active metal oxide, giving rise to the strikingly enhanced active surface area, accelerated electron/ion transport, and further promoted reaction kinetics of OER. Abstract : Based upon metallurgical eutectic solidification control and dealloying inheritance, facile dealloying is developed to fabricate mesoporous Ni‐Fe‐O nanowire network. The composite exhibits exceptionally high electrocatalytic activity and long‐term stability toward oxygen evolution and overall water splitting, which is attributed to the unique mesoporous nanowire network architecture and the synergistic effect of the metal core and the active metal oxide.